North American Monsoon Variability from Paleoclimate Era to Climate Change Projection: A Multiple Dataset Perspective - Carrillo Cruz, Carlos Mauricio (2014)
Descargue el texto completo en el repositorio institucional de la University of Arizona: http://hdl.handle.net/10150/338900